2021
DOI: 10.25115/eea.v39i5.5040
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital transformation on the economic security of Ukraine

Abstract: The article is devoted to the study of the impact of digital transformations on the economic security of Ukraine. The article examines the essence of the digital economy, defines the features of the functioning of the economy in the context of digitalization. Based on the indicators of the international consulting company McKinsey and the World Bank, the authors analyzed the impact of digitalization on the economy, highlighted the main advantages and disadvantages of functioning in the digital economy, systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The mechanism of smoothing the impact of digital transformation on the economic security of the state is determined. Having identified a tool for monitoring the development of a networked digital community -the Network Readiness Index, Spivakovskyy et al (2021) propose a road map of reforms, the main essence of which is to change the structure of management of economic systems at different levels. These changes mean the creation of network management structures with effective management of resources in real time and systematic coordination of participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mechanism of smoothing the impact of digital transformation on the economic security of the state is determined. Having identified a tool for monitoring the development of a networked digital community -the Network Readiness Index, Spivakovskyy et al (2021) propose a road map of reforms, the main essence of which is to change the structure of management of economic systems at different levels. These changes mean the creation of network management structures with effective management of resources in real time and systematic coordination of participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, modern generation Internet technologies include podcasts, blogs, wikis, social networks and other forms of organization and transfer of information (Akkara, Anumula & Mallampalli, 2020;Spivakovskyy et al, 2021). The research objectives include:…”
Section: Introductionmentioning
confidence: 99%
“…Okhrimenko, et al [15] indicated the importance of adjusting the impact of IT for Ukraine to reduce the digital divide between different pop ulation groups. Spivakovsky, et al [16] consider the impact of IT on the economy, in particular in the formation of "digital inequality", which requires smoothing the impact of digital transformations on economic security. Kholiavko, et al [17] indicated that the implementation of IT should be controlled by the state because it has a significant impact on the security of the state in terms of social and economic consequences.…”
mentioning
confidence: 99%
“…Seven countries with the greatest success in economic de velopment (Finland, Switzerland, Sweden, Israel, Singapore, the Netherlands and the United States) take the highest posi tions according to the NRI. Since, according to [16], there is a strong correlation between network readiness and income per capita for the leading countries of the NRI, and the groups of parameters by which this index is determined indicate the lev el of network activity of civil society, it can be asserted that the level of the NRI affects social economy. This is confirmed by the fact that the NRI of these countries is 33 % higher than in other countries with developed economies and, on average, twice as much as in countries with developing economies.…”
mentioning
confidence: 99%